Separate Ionotropic and Metabotropic Glutamate Receptor Functions in Depotentiation vs. LTP: A Distinct Role for Group1 mGluR Subtypes and NMDARs - Latif-Hernandez, Amira; Faldini, Enrico; Ahmed, Tariq; Balschun, Detlef (Frontiers in Cellular Neuroscience, 2016)
Depotentiation (DP) is a mechanism by which synapses that have recently undergone long-term potentiation (LTP) can reverse their synaptic strengthening within a short time-window after LTP induction. Group 1 metabotropic glutamate receptors (mGluRs) were shown to be involved in different forms of long-term potentiation and long-term depression, but little is known about their roles in DP. Here, we generated DP by applying low-frequency stimulation (LFS) at 5 Hz after LTP had been induced by a single train of theta-burst-stimulation (TBS). While application of LFS for 2 minutes (DP2') generated only a short-lasting DP that was independent of the activation of NMDA receptors (NMDAR) and group 1 mGluRs, LFS given for 8 min (DP8') induced a robust DP that was maintained for at least two hours. This strong form of DP was contingent on NMDAR activation. Interestingly, DP8' appears to include a metabotropic NMDAR function because it was blocked by the competitive NMDAR antagonist D-AP5 but not by the use-dependent inhibitor MK-801 or high Mg2+. Furthermore, DP8' was enhanced by application of the mGluR1 antagonist (YM 298198, 1μM). The mGluR5 antagonist (MPEP, 40μM), in contrast, failed to affect it. The induction of LTP, in turn, was NMDAR dependent (as tested with D-AP5), and blocked by MPEP but not by YM 298198. These results indicate a functional dissociation of mGluR1 and mGluR5 in two related and consecutively induced types of NMDAR-dependent synaptic plasticity (LTP DP) with far-reaching consequences for their role in plasticity and learning under normal and pathological conditions.